Efeito da melatonina sobre marcadores teciduais e séricos de dano muscular esquelético induzido por exercício físico - Infante, Nick Alexandre (Universidade Federal de São Carlos, 2021)
Physical exercise can cause muscle damage, commonly called exercise-induced muscle damage (DMIE), triggering several events which will initiate the repair process of this tissue through the activation of satellite cells (CS). The transcription factor PAX7 is used as a CS marker, being expressed during the quiescence, activation and proliferation of these cells. The literature presents some therapeutic resources aimed at reducing damage or even accelerating the muscle repair process, acting on inflammation or oxidative stress. With anti-inflammatory, anti-apoptotic and antioxidant actions, melatonin could be used as one of these therapeutic resources. Experiment I aimed to identify the best prescription for the skeletal muscle damage (PID) induction protocol, using 35 Wistar rats divided into 7 groups: control (CL), protocol 1 (P1), protocol 2 (P2), protocol 3 (P3), protocol 4 (P4), protocol 5 (P5), protocol 6 (P6). The morphological changes found in the white portion of the gastrocnemius muscle through the hematoxylin and eosin technique, the greater depletion in the glycogen content of the same muscle, 24 hours after exercise (P1 -25.24%) compared to the CL group and the high concentrations serum creatine kinase MM (CK-MM) (592.19±190.23 U/L) during the same period demonstrate the efficiency of P1 in causing skeletal muscle damage and justifies its choice for PID. Experiment II aimed to analyze the effects of melatonin on tissue and serum markers of physical exercise-induced skeletal muscle damage, comprising 70 Wistar rats divided into 7 groups: control group (CL), which received vehicle solution (ethanol and NaCl) and were euthanized at 98 days of age and six groups which received melatonin or not immediately after the PID and were euthanized 24, 48 or 72 hours after the exercise (E24), (E48), (E72), (EM24), (EM48) and (EM72). Blood was collected to analyze the concentration of CK-MM and lactate dehydrogenase and white gastrocnemius for quantification of PAX7 expression by immunofluorescence. Data were presented as mean and standard deviation, and the One-way or two-level factorial ANOVA tests were performed with Newman-Keuls post hoc when necessary, as well as the dependent and independent t test, assuming a significance level of 5%. There was an effect of time on serum CK-MM concentrations in animals euthanized 48 hours (F=3.27; p<0.05) compared to rats euthanized 24 and 72 hours after PID. The EM48 group, on the other hand, showed a significant reduction (p=0.010) in the concentrations of this enzyme compared to the E48 group. There was a reduction in PAX7 expression in animals that received melatonin compared to animals that received vehicle solution (F=13.90; p=0.001). Melatonin was able to reduce muscle damage demonstrated by the decrease in the serum concentration of CK-MM, also resulting in a reduction in the expression of PAX7.
Effect of melatonin on tissue and serum markers of exercise-induced skeletal muscle damage
Keywords: Dano muscular esquelético; Melatonina; PAX7; CK-MM; Skeletal muscle damage; Melatonin; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA ENDOCRINA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DO ESFORCO; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA GERAL